P Perbandingan Kadar Flavonoid Total Berdasarkan Perbedaan Konsentrasi Pelarut Etanol Dari Ekstrak Daun Pegagan (Centella asiatica [L] Urban): Perbandingan Kadar Flavonoid Total Berdasarkan Perbedaan Konsentrasi Pelarut Etanol Dari Ekstrak Daun Pegagan (Centella asiatica [L] Urban) - Ali Rakhman Hakim; Mia Audina; Syifa Khairunnisa (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Background: Centella asiatica [L] Urban leaves are empirically used for the treatment of acne. One of the chemical compounds that have pharmacological effects is flavonoids. Polar flavonoid compounds can be drawn using polar solvents based on different polarity levels, which can affect the total flavonoid content obtained. Objective: To determine the effective and optimal concentration of ethanol solvent to obtain total flavonoid content from the leaf extract of gotu kola (Centella asiatica [L.] Urban). Methods: This study used a pre-experimental method with a randomized block design and the research method was maceration extraction, qualitative test of color reagents and thin layer chromatography and determination of total flavonoid content using UV-Vis Spectrophotometry. Data analysis to determine the effect of differences in the concentration of ethanol solvent using the non-parametric Mann-Whitney test. Results: The results of the qualitative test of color reagents and thin layer chromatography were positive for flavonoids. Determination of total flavonoid content of 70% ethanol extract was 4,339 mg QE /g and 96% ethanol extract was 1,895 mg QE /g. The results of data analysis of ethanol solvent concentration had a significant effect on total flavonoid levels. Conclusion: Based on the results of research, 70% and 96% positive ethanol extract contains flavonoid secondary metabolite compounds from the results of measuring the total flavonoid levels of ethanol extract 70% more effective in irradiating flavonoids and ethanol solvent concentrations affect total flavonoid levels.